LAND REGULARIZATION FOR QUILOMBOLA COMMUNITIES IN TOCANTINS: DEMOCRATIC RESISTANCE AND STATE OMISSION IN THE HEART OF BRAZIL - Ribeiro, Jonathan Silva; Haonat, Angela Issa (Seven Editora, 2026)
The land regularization of quilombola territories in the state of Tocantins, although guaranteed by Article 68 of the Transitional Constitutional Provisions of the 1988 Brazilian Constitution, faces significant obstacles to its implementation. The process is hindered by the lack of specific state legislation, limited resources, bureaucratic delays, and political omission. Of the 52 quilombola communities officially recognized by the Fundação Cultural Palmares, only one has had its territory titled, and only through a court decision. This situation reveals a deep gap between legal recognition and the realization of territorial rights. This study uses a mixed methodology (documentary, census, and empirical data) and is grounded in the theoretical frameworks of ethnodevelopment, participatory democracy, and human rights. It highlights the crucial role of social movements, the justice system, and academic production as forms of democratic resistance. A comparison with states like Pará and Maranhão shows how specific legal frameworks can significantly advance quilombola land titling. The study concludes that overcoming state omission requires the establishment of state-level legislation, active participation of quilombola communities, and stronger institutional commitment. Land regularization is not merely a technical or legal issue—it is a matter of social justice, historical reparation, and sustainable territorial development for quilombola peoples in the heart of Brazil.DOI: https://doi.org/10.56238/sevened2026.008-080